Hierarchical porous biochar from shrimp shell for persulfate activation: A two-electron transfer path and key impact factors - Yu, Jiangfang; Tang, Lin; Pang, Ya; Zeng, Guangming; Feng, Haopeng; Zou, Jiajing; Wang, Jingjing; Feng, Chengyang; Zhu, Xu; Ouyang, Xilian; Tan, Jisui (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Prepared biochar (PSS-800) owned hierarchical pore structure.•Adsorption was the key step for the catalytic process.•PSS-800 was dominated by a novel two-electron transfer path.•Porosity and carbon configuration were two crucial impact factors of biochar. Herein, hierarchical porous biochar from shrimp shell (PSS-bio) was prepared and applied for persulfate activation for 2,4-dichlorophenol removal. The pyrolysis temperature was found to play an important role in carbon structure and property modulation, where PSS-bio obtained at 800 °C (PSS-800) exhibited the fastest adsorption capacity and the best catalytic activity with the degradation rates 29 times higher than that of PSS-bio obtained at 400 °C (PSS-400). Further analysis demonstrated that hierarchical pores and carbon configuration were two key impact factors of biochar in AOP. Interestingly, the original free-radical dominated pathway in PSS-400 also changed into a non-radical one (direct two-electron transfer path) in PSS-800, whose efficiency could be somewhat disturbed by pH values, humic acid and anions regardless of their concentrations as low as 5 mM or as high as 500 mM, demonstrating its application potential for the treatment of both highly saline water and organic-rich water.